(untitled) - Lewis, Stephen R. (London, 1970)
This book introduce about the Facts And Artifacts Of Industrial Growth In Pakistan, Instruments Of Economic Policy, The Factors Of Production- Labour, Entrepreneurship And Capital, Principal Policy Instruments And Their Effects On Incentives, The Effects Of Policy On Industrial Growth And Structure, Regional Development And Policy
Keywords: Chính sách công nghiệp,Industrial policy; Pakistan,Pakistan